Acerca de la relación entre los dos tipos de esquemas de las ideas de la razón en la Crítica de la razón pura de Kant - Arias-Albisu, Martín (2012)
“Concerning the Relationship between the Two Kinds of Schemata of the Ideas of Reason in Kant’s Critique of Pure Reason”. The aim of this paper is to examine the relationship between the two kinds of schemata of the ideas of reason introduced by Kant in his Critique of Pure Reason. On the one hand, Kant holds that the schemata of reason are principles, rules or procedures (those of homogeneity, specification and continuity). On the other hand, Kant states that those schemata are objects in the idea or imaginary objects (those of the soul, the world and God). I call the first schemata “dynamic”, and the second ones, “static”. In the first place, I hold that the three dynamic schemata are applied jointly to each one of the static schemata. In the second place, I state that the application of the dynamic schemata to the static schema of the idea of God is a condition of the application of those dynamic schemata to the two other static schemata.